Tela’ah Yuridis Penguatan Lembaga Gadai Syari’ah Dalam Presfektif Peraturan Otoritas Jasa Keuangan Nomor 31/POJK.05/2016 Tahun 2016 Tentang Usaha Pergadaian (“POJK 31/2016”) - Habib, Yahya Abdul Habib; Yumarni, Ani (UIR Law Review, 2025)
Abstract Islamic pawnshops (rahn) are one of the financial instruments that have long been recognized in Islamic tradition and are now formally legitimized through national regulations. The issuance of the Financial Services Authority Regulation (POJK) No. 31/POJK.05/2016 on Pawnshop Business marks an important milestone in strengthening the existence of Islamic pawn institutions, particularly in terms of legal certainty, institutional governance, consumer protection, and their role in national financial inclusion. This study aims to analyze the normative and juridical foundations of Islamic pawnshops as well as the implications of POJK 31/2016 in reinforcing Islamic pawn institutions in Indonesia. The research method employed is normative legal research with a literature study approach, using secondary legal materials such as legislation, DSN-MUI fatwas, books, academic journals, and official reports from OJK and related institutions. The findings reveal that although Islamic pawnshops possess strong legal foundations and are supported by clear regulations, their implementation still faces several challenges, including the prevalence of illegal pawn practices, low levels of financial literacy, complex licensing procedures, and the risks associated with digitalization of services. Therefore, strategic measures are required, such as strengthening supervision, simplifying licensing procedures, enhancing Islamic financial literacy, and developing secure digital innovations. With these strategies, Islamic pawnshops have the potential to become fair, inclusive financial instruments that contribute significantly to the development of a sharia-based national economy. Keywords: Legal Review; Strengthening; Islamic Pawn Institutions; POJK 31/2016.